Alternative Measures of Employee Commitment: Assessment of Predictive Validity for Performance and Turnover. Issue 2 (26th May 2020) - Vance, Robert J.; Jaros, Stephen; Becker, Thomas E.; McKay, Alexander S.
ABSTRACT: Two studies assessed the factor structures and predictive validities of alternative measures of workplace commitments. With the assisted living company and MTurk samples, Study 1 examined factor structures of the affective (AC), normative (NC), and continuance commitment (CC) scales and the unitary commitment scale. The internal structures of the AC and unitary commitment scales were sound, but problems were revealed in the structures of the NC and CC scales. Study 2 compared predictive validities of these scales to a simple one-item measure of attachment. Customer service employees of an energy company completed a commitment questionnaire. Subsequently, supervisors rated their job performance. The company provided objective performance metrics and 7 months of turnover records. Relative weight analyses revealed that predictive validities of the NC, CC, and unitary commitment scales were almost entirely subsumed by the AC scale and the attachment item when all measures competed to explain variance in outcomes. Considering the prevalence of use of the established measures, researchers should be aware of their deficiencies.